A new species of Hemigrammus Gill, 1858 (Characiformes: Characidae) from Río Caura, Venezuela - Benine, Ricardo C. [UNESP]; Lopes, Guilherme A. M. [UNESP] (My University, 2007)
A new characid species, Hemigrammus taphorni, is described from the Río Caura drainage, Venezuela. The new species is distinguished from its congeners by characters related to its color pattern, number of scale rows below the lateral line, teeth morphology, and dorsal-fin length. A brief discussion about the putative relationships of H. taphorni is provided. Copyright © 2007 Magnolia Press.
Keywords: Hemigrammus elegans; Neotropical tetras; Systematics; Characidae; Characiformes; Hemigrammus